Isocyanide Chemistry : Applications in Synthesis and Materials Science - Nenajdenko, Valentine (Weinheim : Wiley-VCH, 2012)
The efficacy of isocyanide reactions in the synthesis of natural or naturallike products has resulted in a renaissance of isocyanide chemistry. Now isocyanides are widely used in different branches of organic, inorganic, coordination, combinatorial and medicinal chemistry. This invaluable reference is the only book to cover the topic in such depth, presenting all aspects of synthetic isonitrile chemistry. The highlyexperienced and internationally renowned editor has brought together an equally distinguished team of authors who cover multicomponentreactions, isonitriles in total.
1.5.1 Isolation and Natural Sources1.5.2 Synthesis of Naturally Occurring Isocyanides; 1.6 Isocyanides Used in the Synthesis of Chiral Polyisocyanides; 1.6.1 Properties; 1.6.2 Synthesis; 1.6.3 Applications; References; 2: General Aspects of Isocyanide Reactivity; 2.1 Introduction; 2.2 Isocyanide-Cyanide Rearrangement; 2.3 Oxidation/Reduction of the Isocyano Group; 2.3.1 Oxidation of the Isocyano Group; 2.3.2 Reactions with Sulfur and Selenium; 2.3.3 Reduction of the Isocyano Group; 2.4 Reactions of Isocyanides with Electrophiles; 2.4.1 Reaction with Acids.
Includes bibliographical references and index.
Print version record.
Keywords: Isocyanides -- Synthesis; Chemistry, Organic; Bioorganic chemistry; Complex compounds; Isocyanides; Organometallic compounds; SCIENCE -- Chemistry -- Organic; Isocyanide; Electronic books